Fe II emission lines in Be stars : I. Empirical diagnostic of physical conditions in the circumstellar discs - Arias, María Laura (2006)
Aims. The Fe II emission lines formed in the circumstellar envelopes (CE) of classical Be stars are studied in order to determine whether they are optically thin or optically thick. We also aim at deriving both average Fe II line excitation temperatures and the extent of their formation region in the CE. Methods. We simultaneously observed several series of Fell emission lines in the λλ4230-7712 Å wavelength interval and the first members of the hydrogen Balmer series of 18 southern classical Be stars. The optical depth regime that controls the formation of the observed Fe II lines and the physical parameters of their CE formation region were studied using the empirical self-aborption-curve (SAC) method. Results. Our calculations give an average value of τo = 2.4 ± 0.9 for the optical depth of the studied Fe II lines, which implies that these lines are optically thick in the CE of Be stars. Qualitative indications that Fell emission lines should be formed in circumstellar regions close to the central star are inferred from the correlations between Fe II emission line widths and V sin i. The application of the SAC method to Fe II emission lines confirms this result, which gives Re = 2.0R⁎ ± 0.8 for the extension of the line-forming region. The proximity of the line-forming region to the central star is also supported by the behavior of the source function of Fen II lines, which rapidly decreases with radii. This prevents the lines from being formed over extended regions and/or far from the star. Finally, the correlations of the central depression in the Balmer emission lines with V sin i are consistent with the flattened geometrical shapes of CEs.